Inflationary Pressure on the Automobile Industry - Amuthan, R.; Ramachandram, A. (Indian Journal of Finance, 2009)
Inflation is the relentless phenomena for every country in the world. In the third week of July 2008, inflation climbed to 11.98%. It may not have crossed the significant mark of 12%. The R.B.I. hoped to contain inflation with a 5 - 5.5% band. However, given the current scenario, RBI has got the target of 7% by March 2009. Stiff hikes in the repo rate and CRR will go a long way in reducing inflation. (Reference- Editorial Column, The Hindu dated Aug.5 2008). However, rising inflation coupled with depreciating US cause tight liquidity conditions and a slowdown in the global economy is an unexpected challenge for the policy makers across the globe.